An analysis of repair practices in L2 Spanish listening comprehension materials with implications for teaching interactional competence. Issue 4 (2nd October 2021) - Batlle, Jaume; Suárez, Maria del Mar
ABSTRACT: Listening materials are commonly developed so students show their understanding of a specific oral discourse. Oral interactions provided in textbooks are resources in which different interactional practices are involved, repair practices being one of these. This article seeks to explore, first, the types of repair practices found in Spanish as a Foreign Language (SFL) textbook listening interactions and, second, the relationship between repairs and other characteristics of the interactions to determine to what extent SFL listening practices are appropriate resources to show examples of repair work and to develop the students' Interactional Competence. Following a Conversation Analysis perspective, 109 repairs in 504 SFL audiotaped listening materials from 18 textbooks are analysed. The results show that repairs are not a common practice in listening materials, other-initiated self-repairs being the most common type of repair work. A disparity is also observed in establishing repair through listening materials depending on the textbook. Some of them include self-repairs together with other interactional features, such as overlapped turns, articulated pauses or response tokens, while other textbooks rarely present any repair work. These findings improve our understanding of the degree of authenticity of listening materials, which might help students develop their interactional competence.